Métodos e práticas de preservação da coleção fotográfica de Vicente Salles - CONCEIÇÃO, Paolla Adriane Alcantara da (2017)
The present work deals with the importance of the preservation of archival documents in the Vicente Salles photographic collection, which is housed in the Museum of the Federal University of Pará (MUFPA), based on a case study based on a bibliographical survey. The instruments used for data collection were an audio interview and a questionnaire. The objective is to analyze the photographic collection, verifying what preservation and conservation techniques were applied in this documentary set and to show the importance of preservation and conservation for the archival photographic collections.